SAT0374 ONSET OF AXIAL SPONDYLOARTHRITIS REPERCUSSIONS ON PATIENTS' SOCIAL AND FAMILY LIFE: RESULTS FROM THE EUROPEAN MAP OF AXIAL SPONDYLOARTHRITIS (EMAS). (2nd June 2020) - Garrido-Cumbrera, M.; Navarro-Compán, V.; Bundy, C.; Mahapatra, R.; Makri, S.; Sanz-Gómez, S.; Christen, L.; Delgado-Domínguez, C. J.; Poddubnyy, D.
Abstract : Background: Axial Spondyloarthritis (axSpA) is associated with a high degree of functional limitation in daily life activities. However, few studies have evaluated the social and family burden from the patient's perspective. Objectives: To describe the impact of axSpA on social and family life since disease onset, and the associated PROs. Methods: Data from 2, 846 unselected patients of the European Map of Axial Spondyloarthritis (EMAS) study through an online survey (2017-2018) across 13 European countries were analysed. The impact of axSpA on social and family life were assessed through four PROs: i) Impact on relationships with the spouse, family, friends, neighbours, and work colleagues since disease onset (5 point Likert scale; 1 "much better" – 5 "much worse"; ii) Frequency of social activities including outings to bars/restaurants, cinema/theatre/museums, practising sports, travel/excursions, and intimate relations since disease onset (5 point Likert scale; 1 "much more" – 5 "much less"); iii) Adaptations made to cope with axSpA since disease onset (yes/no question); iv) The degree of functional limitation in 18 daily activities (3 point Likert scale). Self-reported BASDAI (0-10), spinal stiffness (3-12), functional limitation (0-54), and psychological distress (GHQ-12) were analysed using Pearson's correlation comparing the impact on relationships and frequency of social activities since disease onset. Results: Among 2, 846 participants, mean age was 43.9 years, 61.3% were female, 48.1% had a university degree. The greatest impact on relationships (sum of 'worse' and 'much worse') since disease onset were those with work-colleagues (44.5%), friends (35.6%), and spouse (30.4%). Sport was the activity they reduced the most since disease onset (64.2%), followed by travel/excursions (57.3%) and intimate relationships (56.4%) (Fig. 1 ). 55.5% had purchased comfortable shoes (N = 2748) and 43.9% had made adaptations to their workplace (N = 2651). For those who reported their level of functional limitation in daily activities, the greatest limitations were in physical exercise (85.5%), cleaning the house (84.4%) and using stairs (79.2%) (Fig. 2 ). In the correlation analysis, BASDAI, spinal stiffness, functional limitation, GHQ-12 were associated with a worsening in all of relationships and social activities (p < 0.001) (Table 1 ). Conclusion: For most participants the onset of axSpA marked the worsening of personal relationships in different areas, as well as the reduction of social, leisure, and entertainment activities. Acknowledgments: Funded by Novartis Pharma AG Disclosure of Interests: Marco Garrido-Cumbrera: None declared, Victoria Navarro-Compán Consultant of: Abbvie, Lilly, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Lilly, Novartis, Pfizer, UCB, Christine Bundy Grant/research support from: Has received unrelated honoraria from Abbvie, Celgene, Janssen, Lilly, Novartis, and Pfizer., Raj Mahapatra: None declared, Souzi Makri: None declared, Sergio Sanz-Gómez: None declared, Laura Christen: None declared, Carlos Jesús Delgado-Domínguez: None declared, Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB